Memanfaatkan Metode Kerja Kelompok dalam Model Direct Instruction Untuk Mengoptimalkan Peningkatan Prestasi Belajar Matematika Siswa Kelas 8 Semester I Tahun Pelajaran 2015/2016 DI SMPN 8 Bintan - Ultra Falentina (Universitas PGRI Madiun, 2017)
Mathmatics is one of the lesson which is performed on national final exam. It holds important rule to decide sudents graduation. The fact shown that many students have difficulty in this lesson. They think that mathematics difficult. It makes them have less interest in mathematics.The research method used is class action research. The population of this study is 22 students of VII grade SMPN 8 Bintan. Sampling technique in this study is purposive sampling. The independent variable is group working method in direct instruction model and the dependent variable is mathematics learning performance.The result of this research is passing grade of siclus II increasing to 85 from 72,29. It can be concluded that working method in direct instruction model can increase mathematics learning performance of VII grade SMPN 8 Bintan.